Analisis Perbandingan Kualitas Briket Arang Bonggol Jagung dengan Arang Daun Jati - Dwi Sukowati; Triat Adi Yuwono; Asti Dewi Nurhayati (PendIPA Journal of Science Education, 2019)
AbstraCT[Comparative Analysis of the Quality of Corn Charcoal Briquettes with Teak Leaves Charcoal] This study is a preliminary study that aims to determine the quality of briquettes from different biomass raw materials, namely corncobs and teak leaves. Utilization which is still not maximized from corncobs and teak leaves in the biomass energy field made the initial thought of the study. In addition, both of these raw materials have lignocellulosic contents which are likely to be used as biomass raw materials, especially briquettes. The research method used is an experiment with the research procedure is the manufacture of the two briquettes then the products are analyzed and compared. Both of these raw materials receive the same treatment in the manufacturing process. The composition of the adhesive used is 5% of the main ingredient. The adhesive used is starch. Both briquettes were tested for quality including water content, ash content, volatility, and heating value. The results of testing the water content, ash content, volatile content, the calorific value of corn cobs briquettes and teak leaves charcoal briquettes are, respectively, 3.62% and 5.39% water content; ash content of 4.84% and 3.14%; volatile content of 11.75% and 25.86%; The heating value is 5653.99 cal / g and 7222.95 cal / g. From the results of the analysis, teak leaf charcoal briquettes dominate better quality than corn cobs charcoal briquettes, the water content of teak leaf charcoal briquettes is still higher. When compared with the SNI set value, the two briquettes have met the briquette standards that are suitable to be used as substitutes for alternative fuels.Keywords: Briquette quality; Corn cobs; teak leaves. (Received August 14, 2019; Accepted October 5, 2019; Published October 22, 2019) AbstrakPenelitian ini merupakan penelitian pendahuluan yang bertujuan untuk mengetahui kualitas briket dari bahan baku biomassa yang berbeda yaitu bonggol jagung dan daun jati. Pemanfaatan yang masih belum maksimal dari bonggol jagung dan daun jati di bidang energi biomassa menjadikan pemikiran awal penelitian. Selain  itu, kedua bahan baku ini mempunyai kandungan ligniselulosa yang berpeluang untuk dijadikan bahan baku biomassa khususnya briket. Metode penelitian yang digunakan adalah eksperimen dengan prosedur penelitiannya adalah pembuatan kedua briket kemudian produknya dianalisis dan dibandingkan. Kedua bahan baku ini mendapat perlakuan sama dalam proses pembuatannya. Komposisi perekat yang digunakan sebesar 5% dari bahan utama. Perekat yang digunakan adalah tepung kanji. Kedua briket diuji kualitasnya meliputi kadar air, kadar abu, volatile, dan nilai kalor. Adapun hasil pengujian kadar air, kadar abu, kandungan volatile, nilai kalor dari briket arang bonggol jagung dan briket arang daun jati berturut-turut yaitu, kadar air 3,62% dan 5,39%; kadar abu 4,84% dan 3,14%; kandungan volatile 11,75% dan 25,86%; Nilai kalor 5653,99 kal/g dan 7222,95 kal/g. Dari hasil analisis tersebut, briket arang daun jati mendominasi kualitas yang lebih bagus dibanding dengan briket arang bonggol jagung, kelemahannya kadar air briket arang daun jati masih lebih tinggi. Jika dibandingkan dengan nilai yang telah ditetapkan SNI, kedua briket tersebut telah memenuhi standar briket yang layak digunakan sebagai pengganti bahan bakar alternatif. Kata kunci: Kualitas briket; bonggol jagung; daun jati.